The Token Ekonomy dalam Konseling Islam: Reduksi Perilaku Disruptif pada Siswa - Lina Dwi Puryanti (Da'wah Faculty of UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Disruptive behavior of students in schools is of particular concern to educators and education staff. Disruptive behavior can disturb the class situation, shouting, fighting, being late for class, not paying attention during the learning process, etc. Several studies explain the use of economic tokens. The use of positive and negative reinforcement in the application of economic tokens can be carried out in Islamic counseling services to reduce disruptive behavior in students. This study examines economic tokens in Islamic counseling to reduce disruptive behavior in students. This study uses a qualitative research approach with the method of literature study. The research was carried out by collecting all reading material related to the problem being discussed in this study, then understanding it carefully and thoroughly to produce a finding in the research. Data analysis of the conclusions of this study uses content or content analysis. The study results show that implementing the token economy can be used through Islamic counseling services to reduce disruptive behavior. Using the application of economic tokens can strengthen the desired behavior and reduce disruptive behavior in students. An understanding of the implementation of economic tokens is important before implementing economic tokens in Islamic counseling services.